Methylation analysis of polysaccharides: Technical advice. (15th May 2018) - Sims, Ian M.; Carnachan, Susan M.; Bell, Tracey J.; Hinkley, Simon F.R.
Highlights: Technical advice on glycosyl linkage methodology is provided. Example spectra are shown. Data interpretation methodology is described. Guidelines as to experimental data for publications are proposed. Abstract: Glycosyl linkage (methylation) analysis is used widely for the structural determination of oligo- and poly-saccharides. The procedure involves derivatisation of the individual component sugars of a polysaccharide to partially methylated alditol acetates which are analysed and quantified by gas chromatography-mass spectrometry. The linkage positions for each component sugar can be determined by correctly identifying the partially methylated alditol acetates. Although the methods are well established, there are many technical aspects to this procedure and both careful attention to detail and considerable experience are required to achieve a successful methylation analysis and to correctly interpret the data generated. The aim of this article is to provide the technical details and critical procedural steps necessary for a successful methylation analysis and to assist researchers (a) with interpreting data correctly and (b) in providing the comprehensive data required for reviewers to fully assess the work.